Consumers’ Purchase Intention: The Impact of Live Streaming and Online Customer Review on Onlineshop Areum Art in Medan Perjuangan District - Lina; Sri Rezeki (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2024)
The purpose of this study is to determine the effect of Live Streaming (X1) and Online Customer Review (X2) on Purchase Intention (Y) in Areum Art Onlineshop. This type of research is quantitative research conducted in Medan Perjuangan District with a population of people who already know Onlineshop Areum Art but have never made a purchase. The purposive sampling technique was used in determining the sample and heir et al method was used in determining the sample size, which was 130 respondents. Data collection was carried out by direct observation, literature review and questionnaire results from respondents. Linear regression analysis test is used to analyze data on the three hypotheses in this study. The results show a significant influence of Live Streaming and Online Customer Review on Consumers’ Purchase Intention.